Можливості використання даних супутникових зйомок MODIS для оцінки продуктивності різних видів рослинності та потоків CO2 у системі рослинність — атмосфера (на прикладі території України) - Мовчан, Д.М. (Видавничий дім "Академперіодика" НАН України, 2008)
A growing number of studies has shown that the reflectance changes at 531 nm, associated with the xanthophyll cycle and the related thylakoid energization, are widespread among plant species. The photochemical reflectance index (PRI) has been related with some success to the photosynthetic light use efficiency (LUE). Such a relationship would enable to estimate the photosynthesis by remote sensing data. In this work, the analysis for opportunity using MODIS data for the estimation of processes of photosynthesis for different vegetable cover types is performed. The comparative analysis of the CO2 absorption efficiency by different types of the vegetable cover for a part of the territory of Ukraine is carried out.